PENERAPAN (GMP) DAN (SSOP) PADA USAHA AMPLANG IKAN TENGGIRI WN DI KABUPATEN SAMBAS - Deca Endy Rey (PAKIS JOURNAL INSTITUTE, 2025)
Good Manufacturing Practice (GMP) and Standard Sanitation Operating Procedure (SSOP) are essential guidelines in the food industry to ensure product hygiene and safety. In the marine and fisheries sector, amplang (rice crackers) manufacturing businesses often implement these guidelines to maintain product quality and prevent contamination. The amplang manufacturing process involves several crucial steps: receiving raw materials, filleting, milling, mixing spices and flour, molding, frying, draining, sorting, and packaging. Research has identified several aspects that require improvement, including building structures and facilities, production equipment, hygiene and sanitation facilities and activities, food labeling, record-keeping and documentation, employee training, and improvements to packaging. Specific actions to address these include upgrading building materials to meet hygiene requirements, replacing or maintaining equipment to prevent contamination, installing or improving handwashing and sanitizing stations, updating food labels to comply with regulations, establishing thorough record-keeping practices, providing regular employee training on hygiene standards, and enhancing packaging to better protect the product. Overall, the implementation of GMP and SSOP is still suboptimal and requires improvement to ensure the product is safe and meets food safety standards.